Grammar and culture in the work of Yamuna Kachru. Issue 1 (March 2015) - DAVIS, DANIEL R.; SMITH, LARRY E.; SRIDHAR, S.N.
ABSTRACT This paper examines Professor Yamuna Kachru's construction of grammar in the context of work that adopted a number of different approaches to linguistics, each with its proper data, methodology, and theoretical concerns. These approaches are the standard theory of generative grammar, relational grammar, and grammar from the perspectives of discourse analysis, sociolinguistics, and systemic functional (Hallidayan) linguistics. Throughout her research and publications on grammar and culture, Professor Kachru's work challenges and extends traditional linguistics in a creative and innovative fashion, providing a unique contribution to our understanding of Hindi and English, and to that of grammar and of culture.